INVESTIGATION OF MECHANICAL STRESSES IN THE DRIVE SHAFT OF MV VACUUM CIRCUIT BREAKER - Baida, E. I.; Klymenko, B. V. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2017)
Introduction. In the last 10-15 years a dominant position in the market of medium voltage circuit breakers, vacuum circuit breakers have taken in which as an actuator mono- or bistable actuators with permanent magnets are used. Such circuit breakers are characterized by simplicity of design, high reliability, require preventive maintenance for many years. Development, research and improvement of vacuum circuit breakers are carried out at the Department for Electrical Apparatus, National Technical University «Kharkiv Polytechnic Institute». While working on the circuit breakers, developers have to deal with two related objectives – electrical and mechanical. This paper considers the solution of one of these problems – calculation of mechanical forces in the drive shaft of the vacuum circuit breaker in static and dynamic modes. This work was preceded by the failure of the results of measurements of the prototype circuit breakers’ contacts. Measurements have shown that these values do not match the expected values (there were less than the value of 0.8 to 1 mm). The assumption about the reasons for this discrepancy needed to be detailed checked. The results of the work done are presented in this paper. Purpose. Investigation of static and dynamic mechanical stresses and strains in the drive shaft of the vacuum circuit breaker mechanism to determine its characteristics and material selection. Methods. The investigation of mechanical processes is performed by the finite element method in the COMSOL software package. Results. We obtain the static and dynamic characteristics of the circuit breaker drive shaft: deformations, reaction forces, stresses. These characteristics made it possible to determine the actual course of the contacts, select shaft material and calculate the forces acting on the bearings. Conclusions. It is shown that the contact velocity and contact pressure are different from the theoretical value due to the deformation of the shaft. The forces acting on the thrust bearings dynamically are by 16-39% higher than the static ones. It is assumed that further refinement of the mathematical model takes into account the traction insulators and housing, as well as dynamics of the circuit breaker.